2019
DOI: 10.1002/ejp.1494
|View full text |Cite
|
Sign up to set email alerts
|

Opioids for chronic non‐cancer neuropathic pain. An updated systematic review and meta‐analysis of efficacy, tolerability and safety in randomized placebo‐controlled studies of at least 4 weeks duration

Abstract: Background and Objective This updated systematic review evaluated the efficacy, tolerability and safety of opioids compared to placebo in chronic non‐cancer neuropathic pain. Databases and Data Treatment Clinicaltrials.gov, CENTRAL, PubMed and PsycINFO were searched from October 2013 to June 2019. Randomized controlled trials comparing opioids with placebo and at least 4 weeks double‐blinded duration were analysed. Primary outcomes were pain relief of 50% or greater, disability, tolerability and safety. Effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 50 publications
0
44
0
2
Order By: Relevance
“…One potential mechanism which we were unable to assess is the rise in use of prescription opioid analgesics. Disturbingly, there is no evidence that long-term use of opioid "painkillers" is effective in treating chronic pain (Chou et al 2015;Kissin 2013;Sommer et al 2020). A recent randomized year-long trial actually found that opioids reduced pain less than nonopioids like Tylenol (Krebs et al 2018), and other studies have found that prescription opioids predict more intense pain, lower functioning, higher disability, and higher health care utilization among chronic pain patients (Eriksen et al 2006;Morasco et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism which we were unable to assess is the rise in use of prescription opioid analgesics. Disturbingly, there is no evidence that long-term use of opioid "painkillers" is effective in treating chronic pain (Chou et al 2015;Kissin 2013;Sommer et al 2020). A recent randomized year-long trial actually found that opioids reduced pain less than nonopioids like Tylenol (Krebs et al 2018), and other studies have found that prescription opioids predict more intense pain, lower functioning, higher disability, and higher health care utilization among chronic pain patients (Eriksen et al 2006;Morasco et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, tapentadol was the first opioid approved by the FDA for neuropathic pain associated with diabetic peripheral neuropathy, however, studies on PHN are not available yet. There is insufficient evidence to support or refute the use of other opioids, such as oxycodone, buprenorphine, and tramadol, which have been shown to provide clinically relevant pain relief in highly selected patients with neuropathic pain syndromes [94].…”
Section: Herpetic and Post-herpetic Neuralgiamentioning
confidence: 99%
“…Tramadol ((1 RS ,2 RS )-2-[(dimethylamino)methyl]-1-(3-methoxyphenyl)-cyclohexanol) and tapentadol (3-[(1 R ,2 R )-3-(dimethylamino)-1-ethyl-2-methylpropyl]phenol) are fully synthetic analgesic opioids that synergistically combine mu-opioid receptor (MOR) agonism with monoamine reuptake inhibition, justifying their classification as “atypical opioids” [ 1 , 2 , 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Such dual mechanism of action optimizes analgesia and minimizes opioid-typical side effects, such as drowsiness, nausea, vomiting, constipation, motor incoordination and respiratory depression [ 1 , 2 , 11 , 19 , 27 ], explaining their indications for the treatment of post-surgical, musculoskeletal, inflammatory, cancer and neuropathic pain, as well as mixed pain states [ 1 , 19 , 27 , 28 , 29 , 30 , 31 , 32 ]. Also, owing to the synergistic combination of their mechanisms of action, these opioids allow the dose administered to be reduced without compromising analgesic efficacy, thus reducing the potential for abuse and addiction [ 11 , 33 ].…”
Section: Introductionmentioning
confidence: 99%